Development of Digital-Based Interactive Games to Improve Indonesian Speaking Skills of Grade IV Students of SDN 2 Suntu, Bima City - Sulastri, Sulis; Lastuti, Sri; Akbar , Muh. Rijalul (FKIP - Universitas Riau, 2025)
This research aims to create and implement learning tools in the form of digital-based interactive games to improve the speaking skills of fourth grade students of SDN 2 Suntu, Bima City, with a special focus on conjunction sentence material. The method used in this research is Research and Development (R&D) with the ADDIE approach, which consists of five stages namely analysis, design, development, implementation, and evaluation. The validation results show that this media is declared very feasible by material experts with a percentage of 83% and by media experts with a percentage of 90%. The practicality test showed results reaching 88.7% (for small groups) and 90% (for large groups), which indicated that this media was easy to use and interesting for students. The effectiveness test through N-Gain analysis resulted in a value of 0.79 which is included in the high category, which means there is a significant increase in students' speaking ability after using this media. Therefore, the Interactive game media is declared feasible, practical, and effective as one of the alternatives to digital-based interactive game learning to improve students' speaking ability at the elementary school level.